Aplicación móvil y web e-commerce para la microempresa EcuaSoft de la ciudad de Cañar aplicando el framework JQuery Mobile. - Chogllo Yambay, Manuel Fernando (2023)
This research work corresponds to the implementation of a mobile and web e-commerce application for EcuaSoft microenterprise in the city of Cañar, to present products, from physical stores to virtual stores, for this purpose a quantitative research approach was applied using an interview with the manager and surveys to the users as instruments for data collection, through which the functional and non-functional requirements of the software solution were obtained. In the development of the project, a Visual Studio Code, JQuery Mobile Framework, PostgreSQL, Xamp were used as a local server and as a development methodology the Scrum whose phases are: Start, planning, implementation, review, and retrospective, in addition to the use of the Hotjear tool. to verify user interaction with the mobile and web application through heat maps. The results obtained after the heat map review are: recurring users75%, non-recurring users 25%, bounce rate 3.6%, that is, users visited only one section of the web application, average duration of users on the page 5:16 minutes, most used buttons: article section button, category button, details button, login button and continue button finally it was recorded that 12% of users who visited the page clicked of rage and U-turn, while 88% of users navigated correctly through the interfaces.